Horses for courses - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Folly Sena Kpodar (BP 29, Kpélé-Adéla, Togo) is looking for information on rearing horses. 'I have recently started work at a cattle breeding farm, and I want to expand into horse rearing. Could you please put me in touch with horse rearing...